Tree biomass, wood waste yield, and carbon storage changes in an urban forest (2014)
Urban tree biomass studies are important for estimating urban wood waste yield, carbon sequestration, and other ecosystem goods provided by urban forests. This study quantified urban tree wood waste yield and temporal changes in carbon storage for different land uses using data from permanent monitoring plots and locally developed urban tree and regional allometric biomass equations. Drivers influencing wood waste yields and carbon (C) sequestration were analyzed as was accuracy of available urban tree C storage models. We estimated annual urban tree stem and crown biomass removals at 2 Mega grams (Mg) per hectare, equivalent to approximately 5% of the annual requirements of a 100 MegaWatt bioenergy plant. Urban tree C storage changes, or annual C sequestration, was 29,280 Mg which is equivalent to 5% of all anthropogenic local C emissions in 2008 and twice as much as estimated by an available carbon sequestration model. Greater amounts of wood waste were generated in forests and commercial/institutional areas than residential areas, but differences were not significant and amount removed was only significantly related to the amount of impervious surfaces and maintained grass. Available urban tree C storage models can have errors of 40%. Results can be used to estimate the potential annual supply of city-wide urban wood waste from management, maintenance, land clearing activities, and post-hurricane tree debris removal. Wood waste can be a sustainable urban forest ecosystem service and good; but tradeoffs such as esthetics, soil quality and community preferences should be accounted for as well.